Integrated approach to malaria prevention at household level in rural communities in Wakiso district, Uganda: impact evaluation of a pilot project - Musoke, David (Afr Health Sci, 2018)
BACKGROUND: The integrated approach to malaria prevention, which advocates for the use of several malaria prevention methods at households, is being explored to complement other existing strategies. We implemented a pilot project that promoted the integrated approach to malaria prevention in two rural communities in Wakiso district, Uganda. OBJECTIVES: This paper presents the impact evaluation findings of the project carried out 2 years after implementation with a focus on changes in knowledge and practices on malaria prevention. METHODS: The project evaluation was cross-sectional in design and employed both quantitative and qualitative data collection methods. The quantitative survey was conducted among 540 households (household heads being participants) while the qualitative component involved 4 focus group discussions among community health workers (CHWs). Chi-square test was used to compare quantitative results from the evaluation with those of the baseline while thematic analysis was employed for qualitative data. RESULTS: There was a statistically significant positive change in malaria prevention practices in the evaluation compared with the baseline regarding indoor residual spraying (χ2 = 7.9, p = 0.019), mosquito screening of windows and ventilators (χ2 = 62.3, p = 0.001), and closing windows of houses before 6:00 pm (χ2 = 60.2, p < 0.001). The CHWs trained during the project were found to be highly knowledgeable on the various malaria prevention methods in the integrated approach, and continued to promote their use in the community. CONCLUSION: Findings of the impact evaluation give promise that utilisation of integrated malaria prevention can be enhanced if use of multiple methods is promoted in communities.